An Unusual Case of Lower Extremity Clear Cell Hidradenocarcinoma. (9th April 2020) - Rafols, Marc; Mejia, Odille; Oh, Kei Shing; Bendixen, Blake; Jorge, Irving; Narayanan, Sumana
Abstract : Hidradenocarcinoma (HC) is a rare malignant sweat gland tumor with metastatic potential primarily located in the head, neck, and trunk. We present an unusual case of a large lower extremity Clear Cell HC managed with surgical resection and adjuvant locoregional radiation after excluding lymph node involvement.